Detection, Occurrence and Fate of Emerging Contaminants in Agricultural Environments. (1st October 2015) - Snow, Daniel D.; Cassada, David A.; Bartelt–Hunt, Shannon L.; Li, Xu; D'Alessio, Matteo; Levine, Rachel; Zhang, Yun; Sallach, J. Brett
Abstract : A total of 43 papers published in 2014 were reviewed ranging from detailed descriptions of analytical methods, to fate and occurrence studies, to measuring and predicting biological effects for a wide variety of emerging contaminants likely to occur in agricultural environments. New methods and studies on veterinary pharmaceuticals, natural and synthetics steroids, and antibiotic resistance genes in agricultural environments continue to expand our knowledge base on the occurrence and potential impacts of these compounds. This review is divided into the following sections: Introduction, Analytical Methods, Occurrence and Fate, Antibiotic Resistance Genes, and Risk Assessment.